Pembuatan Keramik Dielektrik Dari Sistem (ZnO-TiO2) Pada Suhu Sinter 1450Â°C dan Karakterisitiknya - Firmansyah, Lutfi; Suhandi, Andi; Syarif, Dani Gustaman (Program Studi Teknik Mesin, Universitas Trisakti, 2007)
Formation Dielectric Ceramic from (ZnO-TiOJ System at 1450C SinteringTemperature and Their Characteristics, Synthesis of dielectric ceramics from (ZnO-TiOJ system at145&C and their characterization had been carried out. This investigation was done in order to knowthepossibility of the application of the ceramics for dielectric ceramics. The ceramics were produced bymixing powder ofZnO and Ti02 with the concentration in such away so that the concentration ofTiO?larger than thestoichiometric concentration ofZn2Ti04 andbysintering at I450